2019
DOI: 10.1111/ffe.13103
|View full text |Cite
|
Sign up to set email alerts
|

Interior induced fatigue of surface‐strengthened steel under constant and variable loading: Failure mechanism and damage modeling

Abstract: Pulsating tension tests with constant amplitude (CA) and variable amplitude (VA) were conducted to investigate the interior failure mechanisms of a carburized Cr steel, and a cumulative damage model with the fine granular area (FGA) formation process was proposed in this study. Such a steel represents the continuously descending S‐N (stress‐number of cycles) curve characteristics associated with inclusion‐FGA‐fisheye induced failure even under variable amplitude. Due to crack growth retardations and accelerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…[1][2][3] Especially in recent days, the concept of very-high-cycle fatigue (VHCF) with over 10 7 cycles fatigue life has been widely concerned, and a series of research results have been obtained. [4][5][6] However, most of the experimental studies are limited to room temperature, and the S-N characteristics, 7-13 failure mechanism, [14][15][16][17][18][19][20][21][22][23][24] and fatigue life evaluation methods [25][26][27][28][29][30][31][32] under elevated temperature environment in VHCF regime are not yet well understood. Therefore, in order to ensure the long-term safety of structural components, the VHCF fatigue characteristics of structural materials in elevated temperature environment still needs to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Especially in recent days, the concept of very-high-cycle fatigue (VHCF) with over 10 7 cycles fatigue life has been widely concerned, and a series of research results have been obtained. [4][5][6] However, most of the experimental studies are limited to room temperature, and the S-N characteristics, 7-13 failure mechanism, [14][15][16][17][18][19][20][21][22][23][24] and fatigue life evaluation methods [25][26][27][28][29][30][31][32] under elevated temperature environment in VHCF regime are not yet well understood. Therefore, in order to ensure the long-term safety of structural components, the VHCF fatigue characteristics of structural materials in elevated temperature environment still needs to be further studied.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors evaluated values of SIF for FGA formation from 4 up to 5 MPa√m. 12,[48][49][50][51] Li et al 52 reported a SIF threshold value of 6.5 MPa√m for the formation of an FGA. In the present study, an average value of ΔK th = 7.0 ± 2.2 MPa√m for all failed specimens was determined using the √area parameter of Murakami 18 and the polygon method to determine the defects' area.…”
Section: Influence Of Defectsmentioning
confidence: 99%
“…This characteristic microstructure area can be called as “optically dark area” (ODA), 9 “granular bright facet” (GBF), 10 “rough granular area” (RGA) 11 or “fine granular area” (FGA) 12 based on different observation methods. Herein, according to previous studies, 13 the term FGA will be used in this paper. Several mechanisms have been proposed to explain the formation of FGA induced by inclusions, such as “hydrogen‐assisted crack growth”, 9 “depressive decohesion of spherical carbides”, 10 and “formation and debonding of fine granular layer” 12 .…”
Section: Introductionmentioning
confidence: 99%